Foreign direct investment, access to finance, and innovation activity in Chinese enterprises - Sourafel Girma; Yundan Gong; Holger Görg (Kiel Institute for the World Economy (IfW), 2008)
This paper investigates the link between inward FDI and innovation activity in China, using a very comprehensive and recent firm level database. We pay particular attention to the impact of domestic access to finance. Our results show that firms with foreign capital participation or those with good access to domestic bank loans innovate more than others do. We also find that inward FDI at the sectoral level is positively associated with domestic innovative activity only if firms engage in own R&D or if they have good access to domestic finance. However, access to finance only plays a role for private or collectively owned firms, less so for state-owned enterprises. Furthermore, we distinguish the effect of sector level inward FDI into technology transfer and FDI affecting domestic credit opportunities and find that the latter is of very little significance for SOEs and is also independent of their access to finance. By contrast, it is an important channel through which FDI affects the innovation of domestic private and collectively owned enterprises.
Keywords: G32; O31; F23; 330; FDI; Finance; China; Innovation; Innovation; Industrielle Forschung; Direktinvestition; Technologietransfer; Verschuldungsrestriktion; China